2022
DOI: 10.3389/fpls.2021.809692
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Soybean Plants to Water Deficit

Abstract: Soybean is an important cash crop in the world, and drought is the main reason for the loss of soybean plants productivity, with drought stress during the most water-sensitive flowering period of soybeans. In this article, drought-tolerant variety Heinong 44 (HN44) and drought-sensitive variety Heinong 65 (HN65) were used as experimental materials. Drought treatment was carried out at the early flowering stage. The method of controlling soil moisture content was used to simulate different degrees of drought, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…The soluble sugar content was determined by following the method of Wang et al [ 43 ]. A 0.1 g sample was ground in 1 mL distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The soluble sugar content was determined by following the method of Wang et al [ 43 ]. A 0.1 g sample was ground in 1 mL distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Two varieties with significant differences in drought resistance at the seedling stage, the sensitive variety Heinong65 (HN65) and the drought-resistant variety Heinong44 (HN44) were selected as experimental materials and provided by the Northeast Agricultural University. The previous physiological tests showed that HN44 had stronger drought resistance than HN65 ( Wang et al, 2021 ). In this experiment, soybean seeds with full-grain, consistent size, and no disease or insects were selected for sowing using the sand pot method.…”
Section: Methodsmentioning
confidence: 98%
“…Drought is one of the most restrictive variables for soybean yield among these abiotic stressors. The yearly all-out crop yield decrease accomplished by dry spells represents more than 50% of all yield misfortunes caused by all pressure factors ( Wang et al, 2021 ). Wei et al (2018) reported the effects of drought pressure at various soybean developmental phases on its yield.…”
Section: Introductionmentioning
confidence: 99%
“…Two cultivars with certain differences in drought tolerance during seed germination were screened in the previous stage: Heinong 65 (HN65) and Heinong 44 (HN44) as test materials. Previous studies have shown that the drought resistance of HN65 is weaker than that of HN44 [ 10 ]. The experiment adopted a method combining river sand potted planting and PEG-6000 osmotic drought stress.…”
Section: Methodsmentioning
confidence: 99%
“…Under drought stress, the contents of abscisic acid (ABA), auxin (AUX), ethylene (ET), salicylic acid (SA), brassinolide (BR), and jasmonic acid (JA) may change significantly to confer plants some drought resistance [ 9 ]. In addition, antioxidant and osmotic regulation systems are also activated, mainly manifested as the enhancement of antioxidant enzyme activity, the accumulation of soluble sugar and soluble protein, and an increase in proline content [ 10 ]. However, changes at the physiological level cannot fully explain the complex mechanism of plant drought resistance, and the synthesis of these enzymes or hormones is usually mediated by certain genes or small molecule metabolites.…”
Section: Introductionmentioning
confidence: 99%